2015
DOI: 10.5152/tjg.2015.4829
|View full text |Cite
|
Sign up to set email alerts
|

The long-term mortality of spontaneous bacterial peritonitis in cirrhotic patients: A 3-year nationwide cohort study

Abstract: Background/Aims: There is no nationwide population-based study for the long-term mortality after single episode of spontaneous bacterial peritonitis (SBP) in cirrhotic patients. Our study showed the short-term and long-term mortalities, and identified the mortality risk of SBP. Materials and Methods: The National Health Insurance Database, derived from the Taiwan National Health Insurance program, was used to collect data from 16,992 cirrhotic patients. These cirrhotic patients were classified into three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Tsung et al, found 30-day mortality in SBP patients of 24.2% and three year mortality of 66.5%.They saw a higher mortality in patients of ascites with SBP, than those without ascites. They found that Cirrhotic patients with SBP have 2.5 fold increase of 3-year mortality, compared to those without ascites [18].…”
Section: Resultsmentioning
confidence: 99%
“…Tsung et al, found 30-day mortality in SBP patients of 24.2% and three year mortality of 66.5%.They saw a higher mortality in patients of ascites with SBP, than those without ascites. They found that Cirrhotic patients with SBP have 2.5 fold increase of 3-year mortality, compared to those without ascites [18].…”
Section: Resultsmentioning
confidence: 99%
“…The 30-day in-hospital mortality of SBP is variable but has been reported to be anywhere between 18% [ 17 ] and up to 31.9% [ 16 ]. Long-term three-year mortality of SBP has been estimated to be around 66.5% in one study [ 18 ], with a 2.5-fold increase in mortality compared to those without ascites. In our study, the unadjusted 30-day in-hospital mortality was 19.7%, which is in the lower spectrum of that reported from recent systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
“…The Spanish study was similar to ours in included time period, analytical methodology, and reported mortality. Another study from Taiwan, using the National Health Insurance Database, examined the nationwide mortality of cirrhotic patients with SBP in 2004 (42). The authors found a 30-day mortality of 24.2%.…”
Section: Discussionmentioning
confidence: 99%